Influence of mean leaf angles and irrigation volumes on water capture, leaching, and growth of tropical tree seedlings - da Silva, Richardson Barbosa Gomes [UNESP]; Gabira, Mônica Moreno; Prado, Débora Zanoni Do [UNESP]; Uesugi, Gláucia [UNESP]; Simões, Danilo [UNESP]; da Silva, Magali Ribeiro [UNESP] (MDPI, 2020)
Research Highlights: The mean leaf angle and crown projection area can be used as criteria for grouping tree seedling species in different irrigation zones in tree nurseries with overhead microsprinkler systems, preventing water and fertilizer waste, and increasing growth. Background and Objectives: There are important gaps in current functional knowledge about how plant architecture, especially the mean leaf angles of tree seedlings, affect water and nutrient solution capture in overhead microsprinkler systems. These gaps contribute to water and fertilizer waste in tree nurseries. This research aimed to ascertain how mean leaf angles affect irrigation water capture, leaching, and the growth of tree seedlings given different volumes of irrigation. Materials and Methods: Nine species of tree seedlings with different mean leaf angles were submitted to four irrigation volumes (8, 10, 12, and 14 mm) applied daily by overhead microsprinklers in a split-plot design completely randomized. The variables leaching fraction, height, stem diameter, shoot, root, and total dry mass, Dickson quality index, crown projection area, root system quality, and leachate electrical conductivity were evaluated. Results: For species with mean leaf angles of −54, 31, 38, 42, 55, 57, and 58◦, the 8 mm irrigation volume was sufficient to produce greater growth and less leaching. For species with angles of −56 and −14◦, the 14 mm irrigation volume was required to produce greater growth. Conclusions: The tree seedling species with positive mean leaf angles facilitate irrigation water and nutrient solution capture, allowing the application of lower irrigation volume. On the other hand, some tree seedling species with negative mean leaf angles hinder irrigation water and nutrient solution capture, requiring the application of higher irrigation volume. When the tree seedling species have a negative mean leaf angle, but the crown projection area is small, the difficulty of water and nutrient solution reaches directly the substrate is attenuated.
Keywords: Container nursery; Irrigation management; Leachate; Microsprinkler irrigation; Plant architecture